Comparative evaluation of 3D-printed and conventional implants in vivo: a quantitative microcomputed tomographic and histomorphometric analysis - Hyemee Suh; Dongseob Lee; Jungwon Lee; Yang-Jo Seol; Yong-Moo Lee; Ki-Tae Koo (Scientific Reports, 2023)
Abstract In recent years, 3D-printing technology to fabricate dental implants has garnered widespread attention due to its patient-specific customizability and cost-effectiveness. This preclinical animal study analyzed the radiographic and histomorphometric outcomes of 3D-printed implants (3DIs) placed immediately after extraction and compared them to conventional implants (CIs). 3DIs and CIs of the same dimensions placed immediately were analyzed at 2, 6, and 12 weeks. The micro-computed tomography (micro-CT) analysis revealed statistically significant differences at 2 weeks in favor of 3DIs over the CIs in terms of bone volume/tissue volume (BV/TV), bone surface/bone volume (BS/BV), trabecular bone pattern factor (Tb.Pf), and structure model index (SMI). At 2 weeks, the mean bone-to-implant contact (BIC) of the 3DIs was greater than that of the CIs; the mean bone area fraction occupancy (BAFO) and the number of Haversian canals of the 3DIs showed no statistically significant differences compared to CIs at 2 weeks. At 6 and 12 weeks, there were no statistically significant differences between the 3DIs and CIs in any parameters. Within limitations, in the early stage of extraction socket healing, the 3DIs demonstrated a higher BIC than the CIs, presenting that 3DIs may be a potential option for immediate placement to enhance osseointegration.